Internalisasi Nilai – Nilai Tawadu` Pada Kitab Risalah Qusyairiyyah Fi‘ilm Al-Tasawwuf Dalam Pembentukan Akhlak Santri Di Pondok Pesantren Darussalam Mukhtar Syafaat Bengkayang - Mustofa, Imam; Nasucha, Juli Amalia (FATAWA: Jurnal Pendidikan Agama Islam, 2023)
This research aims to examine the internalization of tawadhu values ??in the book Risale Qusyairiyyah Fi 'Ilm Al-Tasawwuf in the formation of santri morals at the Darussalam Mukhtar Syafaat Islamic Boarding School. The research method used is qualitative with a case study approach. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation studies. The research results show that the internalization of tawadhu values ??is carried out through three stages, namely transformation, transaction, and transinternalization. In the transformation stage, the values ??of tawadhu are conveyed through the study of the book using lecture, ibrah, and mauidhah methods. At the transaction stage, internalization is carried out through habituation and example in daily activities at the Islamic boarding school. At the transinternalization stage, the values ??of tawadhu have become an inherent character in the students, reflected in their daily attitudes, both inside and outside the Islamic boarding school. The successful internalization of tawadhu values ??is supported by a holistic and integrated education system and a conducive Islamic boarding school environment. The results of this research provide theoretical implications regarding the importance of internalizing values ??in character education and practical implications regarding the need to strengthen character education in Islamic boarding schools and other Islamic educational institutions. This research also provides recommendations for other Islamic boarding schools to make the Darussalam Mukhtar Syafaat Islamic Boarding School a model for internalizing the values ??of tawadhu.